Innovation in the Utilization of Lemon for Phytonutrient Products as an Effort to Increase Income Generation for the Bocek Village Community - Rahmi Annisa; Usman Pagalay; Alvi Milliana; Wirda Anggraini; Fitriyani Fitriyani; M Abbas Arriziq; Roihatul Mutiah (Universitas Lambung Mangkurat, 2024)
Bocek Village is one of the villages in Karangploso District, Malang Regency, East Java Province, which has lemon production reaching 30 tons per month but is not supported by good sales management. Lemon (Citrus lemon) is one of the species of the genus citrus, and it has many benefits, such as anti-inflammatory, antimicrobial, anticancer, and antiparasitic activities. This community service aims to create innovative lemon-based products for phytonutrients to increase income generation for Bocek village, Karangploso district, Malang regency. The method used is ABCD (Asset Based Community Development). The activity was carried out on August 19 2023, in Bocek village, Karangploso district, Malang regency, with the participation of 30 housewives. The results of the activity were successful socialization and demonstrations of lemon slice and lemon squash products that were successfully made, and there were levels of public understanding with good (60%), sufficient (23%), and poor (17%) percentages. So, it can be concluded that training activities on using lemons for phytonutrient products can increase public knowledge and generate income in the future.